Age at menarche and its association with dysglycemia in Korean middle-aged women. Issue 5 (May 2015) - Baek, Tae-Hwa; Lim, Nam-Kyoo; Kim, Min-Ju; Lee, Joungwon; Ryu, Seungho; Chang, Yoosoo; Choi, Yuni; Park, Hyun-Young
Abstract: Objective: Recent studies have demonstrated that earlier menarche is associated with increased risks of prediabetes and diabetes in white women; however, the associations have not been fully explored in Asian populations. We investigated the associations between age at menarche and prediabetes and/or diabetes in Korean middle-aged women. Methods: This was a cross-sectional study of 2, 039 premenopausal and postmenopausal women aged 44 to 56 years who visited the health promotion center for medical checkups. Participants were divided into three groups based on age at menarche: early (<13 y), average (13-16 y), and late (>16 y). Results: The mean (SD) age at menarche was 14.6 (1.6) years. Of 2, 039 women, 820 and 85 women had prediabetes (impaired fasting glucose and/or 5.7%-6.4% glycated hemoglobin) and diabetes, respectively. On logistic regression analysis, earlier menarche was significantly associated with prediabetes (odds ratio [OR], 1.80; 95% CI, 1.24-2.61; P = 0.002), diabetes (OR, 2.43; 95% CI, 1.04-5.69; P = 0.04), and dysglycemia (OR, 1.85; 95% CI, 1.28-2.66; P = 0.001), after adjusting for a number of confounding factors, compared with average age at menarche. On linear regression analysis, earlier age at menarche was significantly associated with increased fasting insulin, homeostatic model assessment for insulin resistance, homeostatic model assessment for β-cell function, body mass index, and waist circumference. Conclusions: Age at menarche is inversely associated with various forms of dysglycemia. A history of earlier menarche may be helpful in predicting prediabetes and subsequent diabetes in Korean women.